2023
DOI: 10.1021/acsami.2c19796
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Assembled Ultrablack Surface with Omnidirectional and Broadband Light Absorption

Abstract: Ultrablack surfaces with stable and omnidirectional light absorption over a wide spectral range are fundamentally crucial for applications concerning strict optical requirements from high-end optical to solar−heat conversion devices. Inspired by nature, we report a needle-like array structure (NAS) prepared by spraying and self-assembling the magnetic composite ink under an external magnetic field. With high structure regularity and small feature size, the NAS presents extremely low hemispherical reflectance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[51][52][53] Moreover, under high tensile strain, the conformation of the network structure is also altered with a more ordered arrangement of the polymer chains, which further weakens the mobility of the dissociative ions and leads to higher GF value. 54,55 The sensitivity of our ionogel sensors is superior to most recently reported ionogel strain sensors operating in air and even more competitive for underwater sensing applications 29,30,32,41,48,50,[56][57][58][59][60] (Fig. 5e).…”
Section: Mechanical and Adhesive Properties Of The Ionogelsmentioning
confidence: 63%
“…[51][52][53] Moreover, under high tensile strain, the conformation of the network structure is also altered with a more ordered arrangement of the polymer chains, which further weakens the mobility of the dissociative ions and leads to higher GF value. 54,55 The sensitivity of our ionogel sensors is superior to most recently reported ionogel strain sensors operating in air and even more competitive for underwater sensing applications 29,30,32,41,48,50,[56][57][58][59][60] (Fig. 5e).…”
Section: Mechanical and Adhesive Properties Of The Ionogelsmentioning
confidence: 63%
“…They found that H 2 O 2 from GOx catalysis and OH from iron-mediated Fenton reactions could catalyse L-arg to release nitric oxide (NO), which subsequently inhibited the Pglycoprotein expression and enhanced intracellular DOX levels, amplifying the chemotherapeutic effect. 123 Despite the effectiveness, the above encapsulating strategies may encounter uncontrolled drug leakage, resulting in side effects to normal tissues. In this regard, the prodrug concept has been introduced.…”
Section: Glucose Metabolism Targeted Nanomedicinementioning
confidence: 99%
“…Furthermore, 𝛼-CD-DOX-NO-DA NPs significantly downregulated the expression of genes related to drug resistance, such as Nme1 (NME/NM23 nucleoside diphosphate kinase 1), Abcc1 (ATP-binding cassette subfamily C member 1), Xrrra1 (X-ray radiation resistance associated 1), and Uvrag (UV radiation resistance associated gene). Overall, Inhibiting drug efflux RSNO HIF-1𝛼 inhibition CT, IT iCPDN [ 156] RONO 2 CT, SDT P@BDOX/𝛽-lapachone-NO-NPs [ 157] L-Arg CT L-Arg@PTX [158] SNP CT, PDT DOX/m-PB-NO@CTS-FA [ 159] RONO 2 CT T-NO/E2-PM [ 160] L-Arg ∖ BTO@DPA [161] BNN6 NF-𝜅B inhibition CT U@Mg-BNN6/DOX [ 162] RONO 2 CT NO-DOX@PDA-TPGS-Gal [163] RSNO ATP level decrease CT 𝛼-CD-DOX-NO-DA NPs [ 164] L-Arg ∖ PIDA [ 165] RSNO CT, PTT MCSN-SNO/DOX [ 166] BNN6 ∖ BNN6@FAPPs [ 167] L-Arg Not mention Catalytic therapy CDT, CT GLDFe/Z-FA [ 168] NONOate PTT, CT IGN Lipo [ 169] L-Arg CT GOD@SiO 2 -Arg [170] L-Arg CT Arg-dots+DOX [ 171] RONO 2 PDT, CT MPEG-PNTC-CA [172] RSNO PTT, CT PDA-PLC/DOX [173] RONO 2 CT CPN [ 174] Furoxan CT (DOX, PSF)@ZnO-DMMA [ 175] NONOate CT D/N-PDA/Hb [ 33d] RSNO CT PEG-PPS-GSNO@DOX [176] L-Arg CT ADL Au@CuS YSNPs [ 177] RSNO CT PNOC-PDA [ 178] RSNO CT pPTX/pCD-pSNO NPs [ 179] Detoxification and self-repair RSNO GSH inhibition SDT BCNR [180] RSNO CT T-SPNA Pt/NO [ 181] RONO 2 CT CTP/CDDP [49b] RSNO Self-repair PTT T-SPMDCTBT/NO [182] NONOates RT SupraNO [113] RBS RT RBS-T-SCNPs [183] RONO 2 RT HNP NPs [ 11c] 𝛼-CD-DOX-NO-DA NPs effectively inhibited P-gp-related biological activity and overcame drug resistance, with a TIR of 86.8% for drug-resistant tumors in mice, which was much higher than that in non-NO-delivery group (28.1%) or non-mitochondriatargeting group (60.6%) (Figure…”
Section: Inhibiting Drug Effluxmentioning
confidence: 99%